SEROLOGICAL OUTCOMES OF TREATMENT WITH 3D-CRT AND IMRT IN LOCALIZED PROSTATE CANCER - Hanif, Shoaib; Osmani, Asif Husain; Malick, Jawaid; Malick, Jawaid (Journal of Ayub Medical College Abbottabad, 2024)
Background: Prostate cancer ranks the second most frequent cancer encountered worldwide in men. Radiotherapy has been effectively used to treat localized prostate cancer. Over the years more effective radiation techniques like 3D-Conformal Radiation Therapy (3D-CRT), Proton Therapy, Intensity Modulated Radiation Therapy (IMRT), and Brachytherapy has been evolved and effectively used to deliver radiation therapy. Herein, we compare serological outcomes of two radiation treatment techniques intensity modulated radiation therapy (IMRT) and 3- dimensional conformal radiation therapy (3DCRT) in localized prostate adenocarcinoma. Methods: It is a cohort study conducted at Department of Oncology, Dr Ziauddin Hospital, Karachi. Patients with localized prostate adenocarcinoma meeting the inclusion criteria were recruited from July 2016 to June 2022, underwent treatment with a total dose >74 Gy using two different advanced radiotherapy techniques, i.e., IMRT and 3D-CRT. Serum PSA levels were assessed prior to treatment, and 6 weeks and 12 months after treatment. Paired t-Test was applied to identify the difference in PSA levels before, and after the treatment. p-value less than 0.05 was taken as significant at 95% confidence interval. Results: A total of 78 patients with 39 in each group. The mean age of patients in 3D-CRT group was 68±10 years while in IMRT group was 68±07 years. Six weeks after initiation of treatment, we observed that both the treatment methods, i.e., 3D-CRT and IMRT reduced the PSA levels significantly p-value = 0.001 respectively. There was no significant difference in the mean of PSA levels on 06th week and 12th months. Furthermore, the analysis of PSA levels at 12th months when compared with the baseline PSA levels came highly significant in both the groups as depicted in paired-t teat analysis of PSA levels with acceptable toxicity. Conclusion: Radiation therapy modalities 3D-CRT and IMRT both showed a significant serological response with minimal or acceptable gastrointestinal and genitourinary toxicities in the 3D-CRT group in comparison to the IMRT group. Although the sample size is relatively smaller, but the results of this study are encouraging to treat those patients on 3D-CRT, who cannot afford more expansive radiotherapy treatment technique like IMRT.